TECHNOLOGY FOR DEVELOPING INFORMATION-ANALYTIC COMPETENCIES IN FUTURE FOREIGN LANGUAGE TEACHERS - Tojiboyeva Shohista Komiljanovna (Web of Journals Publishing, 2024)
This article analyzes the technology of developing informational-analytical competencies of future foreign language teachers in educational processes. The development of informational and analytical competence of future foreign language teachers on the basis of media literacy and information culture should be based on educational principles. As a result of the study of ensuring consistency in the process of teaching students about the information threat and the basics of its elimination, its contours in the methodical system were shown in continuous education. Teaching students to ensure the elimination of information threats should be carried out by the informatics teacher at school. Later, it should be continued by specialist teachers with professional training qualifications in this field. If we take into account the experiences of information threat and its elimination in our country and abroad, Media should take measures in the following directions to protect the student's personal information environment from information threats.
Keywords: “digital”, “computer”, “visual”, “technological”, “communication”, “media”, “information”, “mass culture” and “technocracy”.